Educators' perceptions of the continuous offering of Afrikaans FAL in predominantly Black secondary schools in Johannesburg South - Moloi, Maleshoane Florence (My University, 2022)
Language competence is both the means and the end to educational achievement, and the mastery of a language, in particular, has important cognitive, academic, and societal advantages. The linguistic diversity in South Africa creates an ideal context to provide learners with educational opportunities that promote high levels of linguistic proficiency in their home and additional languages. Unfortunately, a great number of schools have been operating under a language policy that reproduces racial and ethnic inequalities in predominantly Black Ex-Model C schools. Afrikaans continues to dominate as the preferred additional language of teaching and learning in these schools. This study explored the self-disclosed experiences of teachers of Afrikaans First Additional Language in predominantly Black secondary schools in JohannesburgSouth. The critical questions addressed relate to the experiences of teaching Afrikaans FAL, and how learners’ cooperation inside the classroom was impacted, including the socio-emotional relations between teachers and pupils. The study also explored the option of adopting additional African languages to the FAL curriculum. The research was conducted in the Afrikaans FAL classrooms of 2 secondary schools: Secondary School A, which offers only Afrikaans as a first additional language, and Secondary School B which offers more than one first additional language (namely French, IsiZulu and Afrikaans). A preliminary review of related literature suggested that no research has been carried out in Johannesburg-South concerning Afrikaans FAL or in relation to additional language studies. This research is designed to address the gaps that exist and to expose the areas of weakness which are caused by the continuous offering of Afrikaans to Black learners who lack exposure to the language. This study employed qualitative techniques for data collection which included the administering of structured – and semi-structured interviews with educators. Findings revealed that educators are facing challenges in teaching Afrikaans FAL, which negatively impact Black learners' attitudes and results.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Education to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022